Inovasi Dinas Kelautan dan Perikanan Kabupaten Majene dalam Pemulihan dan Peningkatan Perekonomian Rakyat (Survivalitas Nelayan di Tengah Bencana) - Fitriani Sari Handayani Razak; Nurlatifah Raqibah (Journal of Social and Policy Issues, 2023)
The earthquake that occurred in West Sulawesi on January 15 2021 centered 7 km northeast of Majene certainly had an impact on the Majene community, including parts of the Mamuju area and some of the affected Mamasa. Apart from natural disasters, the existence of the Covid 19 virus as a non-natural disaster has had an impact on the people's economy. The research method used in this study is descriptive qualitative using interviews and direct observation at the Maritime Affairs and Fisheries Office of Majene Regency. Majene, which has a coastline of ± 125 km2, makes its people work a lot as fishermen, but in the midst of the disasters (both natural and non-natural) that occur, of course, it has an impact on the people's economy so that it forces local governments, especially the Maritime Affairs and Fisheries Service to innovate so that people can survive in the midst of disaster that befell. This innovation starts with recousing funds/budgets, increasing the yield of fish ponds, working with the private sector in increasing the productivity of skipjack tuna.